A Case Report of Asymmetry of Systolic Anterior Motion of the Mitral Valve, a Not Widely Well-Known but Practically Important Echocardiographic Presentation in Hypertrophic Cardiomyopathy - Ochi, Yuri (CASE (Phila), 2021)
[Figure: see text]